Liver transcriptomics reveals features of the host response in a mouse model of dengue virus infection - Zheng, Wenjiang; Yan, Qian; Li, Zonghui; Wang, Xianyang; Wu, Peng; Liao, Feng; Lao, Zizhao; Jiang, Yong; Liu, Xiaohong; Zhan, Shaofeng; Li, Geng (Frontiers in Immunology, 2022)
Background: Dengue virus (DENV) infection induces various clinical manifestations and even causes organ injuries, leading to severe dengue haemorrhagic fever and dengue shock syndrome. Hepatic dysfunction was identified as a risk predictor of progression to severe disease during the febrile phase of dengue. However, the underlying mechanisms of hepatic injury remain unclear. Methods: A model of dengue disease was established in IFNAR−/− C57BL/6 mice by challenge with DENV-2. Body weight, symptoms, haematological parameters and liver pathological observations in mice were used to determine the effects of DENV infection. Liver transcriptome sequencing was performed to evaluate the features of the host response in IFNAR−/− mice challenged with DENV. Functional enrichment analysis and analysis of significantly differentially expressed genes (DEGs) were used to determine the critical molecular mechanism of hepatic injury. Results: We observed haemoconcentration, leukopenia and liver pathologies in mice, consistent with findings in clinical dengue patients. Some differences in gene expression and biological processes were identified in this study. Transcriptional patterns in the liver indicated that antiviral responses to DENV and tissue damage via abnormal expression of proinflammatory cytokines were induced. Further analysis showed that the upregulated DEGs were significantly enriched in the leukocyte transendothelial migration, complement and coagulation cascades, and cytokine-cytokine receptor interactions signalling pathways, which are considered to be closely associated with the pathogenic mechanism of dengue. IL6, IL 10, ICAM-1, VCAM-1, MMP9 and NLRP3 were identified as biomarkers of progression to severe disease. Conclusions: The interactions of these cytokines, which activate inflammatory signalling, may lead to organ injury and haemoconcentration and even to vascular leakage in tissues, including the mouse liver. Our study identifies candidate host targets that could be used for further functional verification.